Influence of Fungicide Application and Vine Age on Trichoderma Diversity as Source of Biological Control Agents - Guzmán Carro-Huerga; Sara Mayo-Prieto; Álvaro Rodríguez-González; Óscar González-López; Santiago Gutiérrez; Pedro A. Casquero (Agronomy, 2021)
Fungi from the genus Trichoderma have a worldwide distribution and are commonly found in agricultural lands. Further, it has been described as a non-virulent and symbiont microorganism that can contribute to minimize the pernicious effects of pathogens. In the present work we have isolated Trichoderma spp. from bark of grapevine in different orchards in order to determine the influence of fungicide application and vine age on Trichoderma diversity in plant. An opposite correlation between the number of fungicides sprayed per campaign and the diversity of Trichoderma spp. isolates was found. Moreover, the older are grapevine plants the higher is the diversity of Trichoderma spp. isolates. The different Trichoderma strains isolated were tested against Phaeoacremonium minimum, a grapevine trunk pathogen, to evaluate their biocontrol capacity. Three Trichoderma strains shown a significant capacity to control P. minimum and were selected as candidates to be used as biological control agents. In addition, a rapid and easy method for isolating Trichoderma spp. from grapevine plants has been developed, which allowed to determine that the reduction in the amount of pesticide use, together with the preservation of old vineyards, lead to healthier agroecosystems containing higher levels of beneficial microorganisms.